Role of mitochondria in rabies virus-induced oxidative stress - Alandijany, T.; Kammouni, W.; Roy Chowdhury, S. K.; Fernyhough, P.; Jackson, A. C. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Neuronal process degeneration occurs in an experimental mouse model of rabies with hindlimb footpad inoculation of the challenge virus standard-11 (CVS) strain. CVS infection of primary mouse and rat dorsal root ganglion (DRG) neurons has associated axonal degeneration with axonal swellings and neurite outgrowth reduction. The CVSinduced axonal swellings feature protein adducts of 4-hydroxy-2-nonenal (4-HNE), a marker for lipid peroxidation, indicating a critical role of oxidative stress. Western immunoblotting analysis indicated that adducts of 4-HNE expression is also increased in the CVS-infected rat adrenal medulla (PC12) cell line. Mitochondrial dysfunction is one of the most important causes for overproduction and accumulation of reactive oxygen species (ROS). We investigated the effects of CVS infection on several mitochondrial parameters in different cell types (DRG primary neurons, PC12, mouse neuroblastoma (MNA), and baby hamster kidney (BHK-S13) cells) at 72 hrs post infection. The biochemical activity of electron transport system (ETS) complexes (I, IIIII, and IV) and Krebs cycle enzymes (citrate synthase and malate dehydrogenase) were evaluated using a spectrophotometric approach. Krebs cycle enzyme activities were not affected in CVS- versus mock-infected cells. Complex I activity was significantly increased in all CVS-infected cells versus mock-infected controls. Complex I was increased by 30-35% in CVS-infected DRG and PC12 cells, whereas it was increased by 65-75% in MNA and BHK-S13 cells. These values were proportional to the susceptibility of the cells to CVS infection suggesting a direct effect of the CVS infection on Complex I. Complex II-III activity was normal in the infected cells. Complex IV activity was upregulated in all types of CVSinfected cells. However, the increase did not relate to the susceptibility of the cells to the infection, suggesting an indirect effect. We postulate that enhanced Complex IV activity in CVS-infected cells may play a role in avoiding apoptosis. NADH, which is a Complex I-substrate, level was significantly higher in CVS-infected versus mock-infected PC12 cells. NAD+ level in CVS-infected PC12 cells was similar to that in mock-infected controls. Despite the increased activity of ETS complexes, CVS infection reduced the intracellular level of ATP in PC12 cells. The reduced ATP level in CVS-infected DRG neurons may explain, at least in part, the reduction in the neurite outgrowth that was previously observed. We predict that a high mitochondrial inner membrane potential is generated in CVS infection because of increased proton pumping across the mitochondrial inner membrane due to higher activity of Complex I and IV, and decreased proton consumption as indicated by reduced intracellular ATP level. Induction of a high mitochondrial membrane potential promotes electron leakage, primarily at the Complex I site, leading to ROS overgeneration and oxidative stress.